PENGARUH PEMBERDAYAAN PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR KECAMATAN MEDAN TUNTUNGAN - Artha Lumbantobing (LPPM Universitas HKBP Nommensen, 2021)
Public service is one of the products of the government apparatus that is given to the wider community. The implementation of public services is one of the main functions in the administration of government which is the obligation of the government apparatus. Professionalism is a factor that affects the quality of public services so that employees as government officials must work professionally to provide quality public services. This research is a survey research with an explanatory survey or descriptive survey approach. which aims to analyze the effect of professionalism on service quality at the Medan Tuntungan District Office. In this study, the population was all employees of the Medan Tuntungan District Office, amounting to 47 people. Given the relatively small number of populations, the determination of the sample in this study used the total sampling method, which took the entire population as the object of research as many as 47 people. The research instrument used a questionnaire consisting of 30 question items. Hypothesis testing in this study was carried out by simple linear regression analysis with t-test. The results of the study show that the empowerment of employee professionalism has a significant influence on the quality of public services. This is indicated by the value of t-count X (10.126) > t-table (1.98) and sig-p (0.001) < sig-〈 (0.05). The magnitude of the effect of empowering employee professionalism on the quality of public services is 69.5%.